Chronically Ill Czech Patients' Beliefs About Medicines: The Psychometric Properties and Factor Structure of the BMQ-CZ - Matoulkova, Petra; Krulichova, Iva Selke; Macek, Karel; Vlcek, Jiri; Bastecka, Drahomira; Prixova, Martina; Horne, Rob (Therapeutic innovation & regulatory science, 2013)
The main objective of this study was to assess the factor structure and psychometric properties of the Czech translation of the Beliefs about Medicines Questionnaire (BMQ-CZ). It was hypothesized that the 4-factor structure of the BMQ-CZ would be confirmed and that psychometric properties would be verified by using positive or negative correlations with self-reported adherence, illness perceptions, and medication statements. A total of 627 people were approached, and 467 agreed to participate. The sample included chronically ill patients as well as patients seeking allopathic and homeopathic care. As a measure of criterion-related validity, the BMQ-CZ was administered along with the translated Czech versions of the Medication Adherence Report Scale (MARS-CZ) and the Brief Illness Perception Questionnaire (Brief IPQ-CZ) and additional assertions. The factor structure, reliability, and validity of the BMQ-CZ were evaluated. The internal consistency of the BMQ-CZ was satisfactory (Cronbach α = .69-.85). A factor analysis supported the BMQ-CZ's 4-factor structure, and the concurrrent validity of the BMQ-CZ was supported by positive correlations with self-reported measures of adherence and beliefs about medicines and disease. The BMQ-CZ demonstrated sufficient psychometric performance as a self-reported measure of medication beliefs among patients with hypertension, diabetes, and rheumatic disease.
Keywords: chronic illnesses; factor structure; medication adherence; Beliefs about Medicines Questionnaire; psychometric properties